Implementasi Desa Zakat Kabupaten Serdang Bedagai Sumatera Utara dengan Pendekatan Indeks Desa Zakat 2.0 - Isnaini Harahap; Yenni Samri Nasution; Suherman Saragih (Jurnal Ilmiah Ekonomi Islam, 2022)
Contribution of zakat can be further felt by the people who are assisted directly throughout Indonesia which is indirectly related to indonesia's more empowered human development but based on the report of IZN Puskas Baznas 2020 that Organiasai Zakat Manager (OPZ) Serdang Bedagai Regency does not fill the IZN and Impact Assessment so as to describe the conditions in OPZ Serdang Bedagai which is "not good" and data on regional development in North Sumatra. Based on the identification of the above problems, the author can formulate the problem that is the focus of this research: Is Serdang Bedagai Regency worthy to be empowered as a zakat village based on the Zakat Village Index (IDZ)? To answer this formula the author does with a qualitative approach. Based on the results of research analysis of the level of community welfare in the Program at BAZNAS Serdang Bedagai with the perspective of the Zakat Village Index was concluded that the large weight of the value of the Zakat Village Index (IDZ) in Bedagai From 5 dimensions is 0.58 which is good enough so that the refelsi and recompiation from the author that the Muslim community in the Serdang Bedagai area of North Sumatra is considered for assistance. The large weight of the value of the Zakat Village Index (IDZ) in Bedagai deserves to be empowered as a zakat village based on the Zakat Village Index (IDZ) in poverty alleviation this is in line with the government program implementation of the program, especially based on community empowerment that has been compiled by the Center for Strategic Studies / Puskas BAZNAS which serves to assess the process that occurs in the pre-program, at the time the program takes place, and post-program whether a community deserves to be helped and on target with the help of Zakat. So that the results of measuring a village using IDZ with programs are carried out in 20 provinces, 60 districts / cities, 71 subdistricts, and 86 villages / villages. Of the total number of villages measured there are 7 villages are OPZ recommendations, and recommendations of the Ministry of Religious Affairs for the Kampung Zakat program that serdang Bedagai is expected to not be recorded in IZN in 2020 specifically North Sumatra for the Serdang Bedagai region including 8 cities and 25 districts that Organiasai Zakat Manager (OPZ) Serdang Bedagai Regency does not fill the IZN and is expected to be an addition to BAZNAS for future data collection.